1970
DOI: 10.1073/pnas.67.2.696
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Inhibition of Protein Initiation by T4 Phage-Induced Factors

Abstract: Abstract. The phenomenon of selective translation of T4 template RNA by ribosomes from T4-infected cells, or factors derived therefrom, has been extended to studies on the initiation of protein synthesis. A high-salt extract derived from T4-infected ribosomes inhibits the formation of initiation complexes of MS2 and Escherichia coli template RNA with uninfected ribosomes while efficiently supporting the formation of initiation complexes with T4 template RNA. T4 factors also permit T5 template RNA to bind to E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1971
1971
1977
1977

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Mengovirus might also interfere with the synthesis of late vaccinia virus messenger RNA, once early messenger and early proteins were apparently synthesized. It may be, however, that each virus produces a "translation inhibitory protein" similar to that described in bacterial cells infected with T-even phages (8,9,11,17,26). If such was the case, the ribosomes of the cell would eventually be unable to synthesize effectively either host, mengovirus or vaccinia virus proteins, and the result would be the double interference reported here.…”
Section: Discussionmentioning
confidence: 95%
“…Mengovirus might also interfere with the synthesis of late vaccinia virus messenger RNA, once early messenger and early proteins were apparently synthesized. It may be, however, that each virus produces a "translation inhibitory protein" similar to that described in bacterial cells infected with T-even phages (8,9,11,17,26). If such was the case, the ribosomes of the cell would eventually be unable to synthesize effectively either host, mengovirus or vaccinia virus proteins, and the result would be the double interference reported here.…”
Section: Discussionmentioning
confidence: 95%
“…It is difficult to decide between these alternatives. Most workers favor the second mechanism, largely because of experiments in which it was shown that ribosomes isolated from cells 12 min after T4 infection were unable to translate or bind f2 RNA, but could translate normally poly uridylic acid or late T4 mRNA (5,16,19). These cell-free experiments must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of Escherichia coli by the deoxyribonucleic acid (DNA) phage T4 results in cessation of host ribonucleic acid (RNA) and protein synthesis. Mechanisms proposed to account for this include alterations in the host membrane (6,8), synthesis of a T4-specific factor for initiation of transcription (30), a loss of certain host transfer RNA (tRNA) species (29) with replacement by phage-specific tRNA species (4,28), and a change in the factors required for initiation of messenger translation (5,16,19,20).…”
mentioning
confidence: 99%
“…The assigned codons for leucine are UUA, UUG, CUU, CUC, CUA, and CUG. The reaction system was essentially the same as described by Klemi et al (11) except that no added tRNA was present. An S165 soluble supernatant fraction, derived from 1/4 log E. coli B cells, was treated with DEAE-cellulose to remove endogenous tRNA and dialyzed (14).…”
Section: Resultsmentioning
confidence: 99%